The labor-market returns to community college degrees, diplomas, and certificates - Christopher Jepsen; Kenneth R. Troske; Paul A. Coomes (Institute for the Study of Labor (IZA), 2012)
This paper provides among the first rigorous estimates of the labor-market returns to community college certificates and diplomas, as well as estimating the returns to the more commonly-studied associate's degrees. Using administrative data from Kentucky, we estimate panel-data models that control for differences among students in pre-college earnings and educational aspirations. Associate's degrees and diplomas have quarterly earnings returns of nearly 2,400 for women and 1,500 for men, compared with much smaller returns for certificates. There is substantial heterogeneity in returns across fields of study. Degrees, diplomas, and - for women - certificates correspond with higher levels of employment.
Keywords: J24; 330; returns to school; community college; diploma; certificate; Bildungsabschluss; Bildungsertrag; Panel; Schätzung; Kentucky; USA